Sustainability in the automotive industry, importance of and impact on automobile interior: Insights from an empirical survey - Wanja Wellbrock; Daniela Ludin; Linda Röhrle; Wolfgang Gerstlberger (International Journal of Corporate Social Responsibility (JCSR), 2020)
Sustainability is currently one of the main issues in all media and in society as a whole and is increasingly discussed in science from different sides and areas. Especially for the automotive industry, sustainability becomes more and more important due to corporate scandals in the past and topics such as electric motors, lightweight construction and CO2 emission reduction are key issues. Although the focus is primarily on other components, the interior cannot be neglected either in terms of sustainability. Interior is the most frequently seen part of the car by the driver. Therefore, e.g. the use of natural fibres especially for premium brands can only be considered in connection with highest standards regarding practical and aesthetical aspects. Consequently, the following research question arises: How do the three pillars of sustainability (economical, ecological and social issues) influence interior development at premium brand manufacturers and how do customers accept sustainable solutions? The focus of the paper is exclusively on premium brands due to the higher spread of sustainability effects compared to volume brands. A quantitative study is carried out to determine the expectations on the customer side regarding more sustainability in the automotive industry in general and in the interior sector in particular and to derive corresponding challenges and potentials for original equipment manufacturers.
Keywords: 650; Sustainability; Automotive industry; Interior; Innovation